Space standards and housing design: typological experimentation in England and Chile. Issue 1 (2nd January 2022) - Jacoby, Sam; Arancibia, Alvaro; Alonso, Lucia
Abstract : Space standards are a deliberately technocratic translation of housing experience, use, and demand into measurable minimum floor areas and dimensions by calculating standard furniture sizes, circulation, and activity zones in a dwelling. This paper discusses how space standards register regulatory cultures and affect housing design and perceptions of housing quality from a design research perspective. The definition and enforcement of standards depend on local design governance approaches. Housing standards are of particular importance to the protection of minimum subsidised housing supply in dualist rental systems with differentiated regulations, due to greater inequalities between private and subsidised housing sectors. This is characteristic of countries with neoliberalised housing access. Two archetypical cases are discussed here: England, whose privatisation of council housing is considered exemplary for Western neoliberal housing policy; and Chile, who is seen as the main Latin American neoliberal model. This comparison explores how neoliberal processes in housing relate to space standards, wider laissez-faire housing and social welfare histories, and design experimentation in subsidised housing. It further deals with the common issues of affordable housing in market-driven contexts, such as the peripheralisation of areas with less infrastructures and services, residualisation of social housing tenure, typological stigmatisation or preferences, homeownership prioritisation, and private-sector support through subsidies. The discussion of housing design and space standards connects problems of design governance to technical, legal, and socio-spatial discourses, through which responses to cultural, social, and economic contexts, as well as changing modes of living, can be analysed.